Narrativas de paz, voces y sonidos: Análisis de la paz en Colombia, desde la comunicación - Cruzco, Deris (Quórum Académico, 2020)
Ignacio ´Iñaki´ Chaves G. Beatriz E. Múnera B. Gabriel A. Ruiz R. (Coords.)